Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing 2015
DOI: 10.18653/v1/d15-1069
|View full text |Cite
|
Sign up to set email alerts
|

Key Concept Identification for Medical Information Retrieval

Abstract: The difficult language in Electronic Health Records (EHRs) presents a challenge to patients' understanding of their own conditions. One approach to lowering the barrier is to provide tailored patient education based on their own EHR notes. We are developing a system to retrieve EHR note-tailored online consumer oriented health education materials. We explored topic model and key concept identification methods to construct queries from the EHR notes. Our experiments show that queries using identified key concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One study has shown that linking medical terms in EHR notes to Wikipedia pages can improve patient’s comprehension [ 51 ]. Moreover, many methods have been proposed to identify important or potentially unfamiliar medical terms [ 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…One study has shown that linking medical terms in EHR notes to Wikipedia pages can improve patient’s comprehension [ 51 ]. Moreover, many methods have been proposed to identify important or potentially unfamiliar medical terms [ 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Concept identification indexing approaches have been used for information retrieval in different domains. Zheng and Yu (2015) developed a system for medical information retrieval. The medical terms in electronic health records (EHRs) are often hard for patients to understand.…”
Section: Concept Identification and Retrievalmentioning
confidence: 99%
“…Furthermore, their processing through statistical techniques alone appears insufficient since they encompass several domain-specific medical concepts [2] that require making use of extrinsic knowledge for their deciphering [3]. This forms a crucial challenge for Medical Information Retrieval (MIR) systems that aim to find matches between medical documents and their corresponding queries in the same domain [4][5][6] and motivates the use for language resources when further expanding these queries [7,8]. Recently, MIR systems have shifted to exploiting medical semantic resources and ontologies in an attempt to capture knowledge in this domain through formally and explicitly defining medical concepts, instances, as well as semantic and taxonomic relations that link related concepts.…”
Section: Introductionmentioning
confidence: 99%